(untitled) (The Macau Ricci Institute Journal, 2023)
Historically, both Macau and Guangzhou were ports of encounter where some of the first Africans landed in China, but not necessarily as free individuals. Arab traders and Portuguese seafarers of centuries past were responsible for the earliest transfer of black manpower to China’s southern regions. Because of this peculiar situation, we cannot talk of a proper cultural dialogue between Chinese and Africans. Since the early 2000’s, we have witnessed the formation of the Forum for China-Africa Cooperation and, with special implications for Macau, the creation of the Forum for Economic and Trade Co-operation between China and Portuguesespeaking countries. For over thirty years (1991–2023), Africa has been the destination of China’s first overseas visit at the beginning of every year. China and African countries met ever-more frequently at ever-higher levels and registered record-breaking trade deals. Fast-forwarding to the present, we notice some worrying signs. Is the golden period of China-Africa engagement already behind us? We are interested in the cultural dialogue between China and Africa – in Macau and in Guangzhou – considering Covid and the difficult accommodations made to fight it.